Firearm ownership for protection in the USA, 2023: results from a nationally representative survey - Degli Esposti, Michelle; Sokol, Rebeccah L; Lee, Daniel B; Wiebe, Douglas J; Cunningham, Rebecca M; Hawryszkiewycz, Alice; Carter, Patrick M (Injury prevention, 2025)
ObjectiveThis study aims to characterise the motivations of firearm owners and examine whether firearm ownership motivations and carriage varied by state stand your ground law status. MethodsUsing a nationally representative survey of US adults in 2023, we asked firearm owners (n=2477) about their firearm motivations and behaviours, including reason(s) for ownership.ResultsOf all firearm owners, 78.8% (95% CI 76.0% to 81.0%) owned a firearm for protection, and 58.1% (95% CI 54.3% to 62.0%) carried a firearm outside their home in the last 12 months. Firearm ownership for protection was not significantly associated with stand your ground laws, but firearm carriage was more prevalent in states with stand your ground laws (50.1% (95% CI 47.0% to 53.0%) vs 34.9% (95% CI 25.0% to 46.0%)). Gender (women) and race (minority groups) emerged as key correlates for firearm ownership for protection (vs other ownership motivations). For example, black and Asian women (98.8%) almost exclusively owned firearms for protection.ConclusionsProtection was the dominant reason for firearm ownership in 2023, motivating 65 million Americans to own firearms and appealing to different strata of the population.